Dark tide - Donnelly, Jennifer (Donnelly, Jennifer. Waterfire saga, 2015)
"Astrid struggles with a shameful secret, Ling discovers courage in a prison camp, and Serafina lines up allies to help fight the final battle for her underwater realm"--